Effective Technologies and Modular Plants for Processing of Ores of Rare and Noble Metalls - Victor Beloborodov; Konstantin Fedotov; Anatoly Potyomkin (International Mineral Processing Congress, 2003)
"There are areas in Russia, which cover huge territories and they are north, and Siberia. These difficult to access regions with cold climate are rich in a great number of distant deposits of valuable and rare metals, gold and platinum. The development of such deposits requires highly effective technologies of mineral processing which could be realized in modular and quick-built processing plants.The work presented includes the results of long term research in the development of new technologies of processing of zirconium (in the form of rare mineral Baddeleyite – natural zirconium dioxide) bearing ore of the Kovdor deposit which is located in the Polar region of the Kola peninsular and also in Siberia deposits of of ledge ores of gold."